2005
DOI: 10.1111/j.1365-201x.2005.01434.x
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo model for gastric physiological and pathophysiological studies in the mouse

Abstract: This model has great potential for investigations of gastrointestinal physiology and pathophysiology and can be applied for Helicobacter pylori infection studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
(68 reference statements)
2
11
0
Order By: Relevance
“…A relevant question is whether the acid-base values in Ringer solution-treated mice are to be considered abnormal, i.e., acidemic, or not. Typical values for pH and PCO 2 previously reported in isoflurane-anesthetized spontaneously breathing mice have ranged, respectively, from 7.35 and 39 mmHg (27) to 7.25 and 49 mmHg (8). These values are in fair agreement with those in the Ringer solutioninfused mice found here.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A relevant question is whether the acid-base values in Ringer solution-treated mice are to be considered abnormal, i.e., acidemic, or not. Typical values for pH and PCO 2 previously reported in isoflurane-anesthetized spontaneously breathing mice have ranged, respectively, from 7.35 and 39 mmHg (27) to 7.25 and 49 mmHg (8). These values are in fair agreement with those in the Ringer solutioninfused mice found here.…”
Section: Discussionsupporting
confidence: 81%
“…However, this anesthetic is not without side effects. A commonly reported side effect of isoflurane anesthesia in mice is disturbance of the acid-base balance, e.g., acidosis (8,13,24,31).…”
mentioning
confidence: 99%
“…We have previously shown in a rat model (3) and in this mouse model (16) that the mucus layer can be divided into two layers: one that can be removed (designated loosely adherent) and one that cannot be removed by mechanical means without destroying the epithelial layer (the firmly adherent layer). From another study, we (28) have also concluded that it is the firmly adherent layer that is important for the protection against luminal acid, because it is in this layer that the pH gradient is formed.…”
Section: Discussionmentioning
confidence: 99%
“…Blood flow was measured with laser-Doppler flowmetry equipment (Periflux instruments Pf3 and Pf4001, Perimed; Stockholm, Sweden), which has previously been used to study microcirculatory blood flow of the gastric mucosa in the mouse model (16). The laser probe was held in a fixed position in the chamber solution at a distance of 1-2 mm above the mucosa by a micromanipulator.…”
Section: Blood Flow Measurementsmentioning
confidence: 99%
See 1 more Smart Citation